ChemInform Abstract: Crystal Structure and Magnetic Ordering Transitions in CeNiIn4, EuNiIn4 and EuCuIn4. Issue 3 (January 2015) - Schnelle, Walter; Kremer, Reinhard K.; Hoffmann, Rolf‐Dieter; Rodewald, Ute Ch.; Poettgen, Rainer
Abstract CeNiIn4 is prepared by arc‐melting of the elements followed by annealing at 970 K for two weeks.